Seasonal, Interannual and Long-term Sea-level Changes in the Arabian Gulf - Abdulla , Cheriyeri Poyil (Current Advances in Geography, Environment and Earth Sciences Vol. 5, 2022)
The present chapter explores the seasonal, interannual, and long-term sea-level changes in the Arabian Gulf. Tides, winds, and density-driven currents are the primary drivers of circulation in the Arabian Gulf. The sea level is relatively high during fall and low during spring, with a maximum during November and a minimum during April. The sea-level variability in the Arabian Gulf is considerably different from or nearly opposite to the pattern of sea-level changes in the adjacent marginal basin (Red Sea). Using Principal Component Analysis, the analysis of low-passed sea-level has shown that the first mode of variability explains 87.9% of the long-term variability. Long-term linear sea-level trends in the Northern Arabian Gulf are 2.58 mm/year and 3.14 mm/year, respectively, with an overall average of 2.92 mm/year. The long-term linear trend in sea-level for the post-2000 period at the northern and southern regions are 4.06 mm/year and 4.44 mm/year, respectively, with a basin average trend of 4.29 mm/year. The numerical estimates for the RCP2.6, RCP4.5, and RCP8.5 scenarios reveal a predicted rise in sea level in the Arabian Gulf of 8.1 cm, 1.3 cm, and 6.8 cm by 2050, and 16.9 cm, 17.7 cm, and 39.1 cm by the end of the century, respectively.